2021
DOI: 10.1021/acssynbio.1c00244
|View full text |Cite
|
Sign up to set email alerts
|

Solving 0–1 Integer Programming Problem Based on DNA Strand Displacement Reaction Network

Abstract: Chemical reaction networks (CRNs) based on DNA strand displacement (DSD) can be used as an effective programming language for solving various mathematical problems. In this paper, we design three chemical reaction modules by using the DNA strand displacement reaction as the basic principle, with a weighted reaction module, sum reaction module, and threshold reaction module. These modules are used as basic elements to form chemical reaction networks that can be used to solve 0−1 integer programming problems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Previous research has demonstrated that by designing appropriate DNA SDR, one can approximately realize all chemical reactions with ideal forms [ 20 , 21 ]. For example, in [ 22 ], SDR-based DNA switching circuits were designed for digital computing; in [ 23 ], the authors developed a time-sensitive molecular circuit based on SDR, called the cross-inhibitor, which can execute mutual inhibition; in [ 24 , 25 ], DNA strand displacement for microRNA detection was investigated; in [ 26 ], the authors analyzed the morphological manipulation of DNA gel microbeads with biomolecular stimuli by using SDR; in [ 27 ], the authors proposed an SDR-based chemical reaction network to solve 0–1 integer programming problems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that by designing appropriate DNA SDR, one can approximately realize all chemical reactions with ideal forms [ 20 , 21 ]. For example, in [ 22 ], SDR-based DNA switching circuits were designed for digital computing; in [ 23 ], the authors developed a time-sensitive molecular circuit based on SDR, called the cross-inhibitor, which can execute mutual inhibition; in [ 24 , 25 ], DNA strand displacement for microRNA detection was investigated; in [ 26 ], the authors analyzed the morphological manipulation of DNA gel microbeads with biomolecular stimuli by using SDR; in [ 27 ], the authors proposed an SDR-based chemical reaction network to solve 0–1 integer programming problems.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of DSD, complex applications are implemented. Examples include solving the square root calculator of a 4-bit binary input, handwriting recognition, signal amplifier, oscillator, decision-making machine, neural networks, , disease detection, and 0–1 integer programming problem …”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 18 works, 33,34 disease detection, 35 and 0−1 integer programming problem. 36 Although DSD technology has shown great potential in the construction of large-scale molecular networks, a multilevel cascade increases the complexity of the circuit and causes leakage between the logic gates. Inspired by redundant error correction methods in electrical engineering, Wang et al 37 used the DNA chain energy by involving logical redundancy.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of any influenza virus is an important indicator for pandemic risk. Computational tools in the field of machine learning have been used to identify phenotype of biological data [ 23 , 24 ]. Machine learning techniques gain knowledge from viral protein sequences and represent viruses by optimal features [ 25 ].…”
Section: Introductionmentioning
confidence: 99%